Pengalaman Ibu Merawat Balita dengan Infeksi Saluran Pernapasan Akut: Studi Fenomenologi - Filia Sofiani Ikasari; Iis Pusparina (PT.Mantaya Idea Batara, 2024)
Acute Respiratory Infection (ARI) is an infectious disease that is the main cause of mortality and morbidity in children under five years of age (toddlers). Mothers play an important role in determining the decisions and actions needed in caring for toddlers with ARI at home. Even though the ARI treatment given to toddlers from health service facilities is successful, if it is not treated further at home, the toddler will be at risk of experiencing ARI again, so mothers play an important role in caring for toddlers with ARI. This research is qualitative research with a phenomenological design. The participants who participated in this research were 5 mothers who had toddlers with a history of ARI. The sampling technique used was snowball sampling. Data collection used the in-depth interview method to explore mothers' experiences in caring for toddlers with ARI. The data analysis used is Colaizzi data analysis. The results of this study identified 4 themes, namely actions taken by mothers to overcome the symptoms of ISPA, difficulties faced by mothers in caring for toddlers with ARI, children's responses when receiving treatment at home, and actions taken by mothers to prevent ARI. The conclusion obtained from this research is that 4 themes were obtained from mothers' experiences in caring for toddlers with ARI